2013
DOI: 10.1089/omi.2012.0079
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Drug-Induced Hepatotoxicity in Primary Mouse Hepatocytes Using Acetaminophen, Amiodarone, and Cyclosporin A as Model Compounds: An Omics-Guided Approach

Abstract: Drug-induced hepatotoxicity is a leading cause of attrition for candidate pharmaceuticals in development. New preclinical screening methods are crucial to predict drug toxicity prior to human studies. Of all in vitro hepatotoxicity models, primary human hepatocytes are considered as 'the gold standard.' However, their use is hindered by limited availability and inter-individual variation. These barriers may be overcome by using primary mouse hepatocytes. We used differential in gel electrophoresis (DIGE) to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…2012; van Summeren et al. 2013). Actually, some data in mice indicated that ER stress was a relatively late event after APAP intoxication (500 mg/kg), being significant only 12 hours following APAP administration (Hur et al.…”
Section: Introductionmentioning
confidence: 99%
“…2012; van Summeren et al. 2013). Actually, some data in mice indicated that ER stress was a relatively late event after APAP intoxication (500 mg/kg), being significant only 12 hours following APAP administration (Hur et al.…”
Section: Introductionmentioning
confidence: 99%
“…The proteins differentially expressed after exposure to CsA in HepG2 and primary mouse hepatocytes, were retrieved from previous studies [9,10]. The Panther classification system (http:// www.pantherdb.org) was used to compare the effect of CsA upon the protein expression in HepG2, primary mouse hepatocytes and in vivo mouse liver.…”
Section: Functional Classificationmentioning
confidence: 99%
“…Previously we investigated the proteome of HepG2 cells and primary mouse hepatocytes after exposure to three well-defined hepatotoxicants [9,10]. These were acetaminophen, amiodarone and cyclosporin A (CsA), of which CsA generated the most prominent response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations